Uncommon presentation, rare complication and previously undescribed oncologic association of pheochromocytoma; the great masquerader. (5th April 2018) - Lawrence, David; Salimian, Kevan; Leucker, Thorsten; Martin, Seth
Abstract : We describe the case of a 67-year-old man presenting with ventricular tachycardia (VT) and systolic heart failure secondary to a left adrenal phaeochromocytoma. After treatment with amiodarone, the patient's VT resolved. However, his course was complicated by femoral deep venous thrombosis secondary to an incidentally discovered dedifferentiated liposarcoma of the thigh, for which he was prescribed a course of enoxaparin. The patient was discharged with plans for adrenalectomy following achievement of sufficient preoperative heart rate and blood pressure control with alpha-adrenergic receptor blockade, but re-presented to an outside facility in haemorrhagic shock, where he ultimately expired. Autopsy determined his death to be caused by spontaneous haemorrhage of the phaeochromocytoma. Cardiac manifestations, complications and oncological associations of phaeochromocytoma are discussed.